MicroRNA signatures of CD4+ T cell subsets in healthy and multiple sclerosis subjects determined by small RNA-sequencing - Culina, Slobodan; Commère, Pierre-Henri; Turc, Elodie; Jouy, Axel; Pellegrini, Sandra; Roux, Thomas; Hasan, Milena; Monot, Marc; Michel, Frédérique (Journal of neuroimmunology, 2025)
Diverse CD4+ T cell subsets with specialized functions operate at different phases of the immune response. Among these are phenotypically and functionally characterized naïve, central memory (CM), effector memory (EM), and regulatory (Treg) cells. Using small RNA-sequencing, we have profiled miRNAs in these cell subsets from healthy subjects and untreated patients with relapsing-remitting multiple sclerosis (RRMS). MiRNA genomic clustering and abundance were also investigated. From the 60 most differentially expressed miRNAs, broad and highly selective core signatures were determined for naïve and memory cells at homeostasis, while miR-146a-5p was strongly upregulated in Treg cells. In line with other studies, a 5-miRNA core was identified for naïve cells (miR-125b-5p, miR-99a-5p, miR-365a-3p, miR-365b-3p, miR-193b-3p). In memory cells, a number of identical miRNAs were more expressed in EM than CM cells, supporting the progressive T cell differentiation model. This was particularly the case for an 8-miRNA core (members from miR-23a∼27a∼24–2, miR-23b∼27b∼24–1, miR-221∼222 clusters, miR-22-3p, miR-181c-5p) and for the large ChrXq27.3 miR-506∼514 cluster. Interestingly, most of these miRNAs were reported to negatively regulate cell proliferation and survival. Finally, we found that the miRNA core signatures of naïve and memory CD4+ T cells were conserved in RRMS patients. Only few miRNAs were quantitatively modified and, among these, miR-1248 was validated to be downregulated in EM cells. Overall, this study expands and provides novel insights into miRNA profiling of CD4+ T cell subsets that may be useful for further investigations. [Display omitted] •miRNA profiles of naïve, central memory, effector memory, and regulatory CD4+ T cell subsets in healthy subjects•Conserved miRNA cores in untreated patients with relapsing-remitting multiple sclerosis•A small set of miRNAs is differentially expressed between patients and controls•One downregulated miRNA may be a candidate disease marker